Approximation of a Continuous Function by a Sequence of Convolution Operators via a Matrix Summability Method Using Ideals - Ghosh, Rima; Dutta, Sudipta (Sarajevo Journal of Mathematics, 2024)
In this paper, in the line of Duman [7], we deal with Korovkin type approximation theory for a sequence of positive convolution operators defined on C[a,b], the Banach space of all real valued continuous functions on [a,b] endowed with the supremum norm ||f||=_x[a,b]|f(x)| for fC[a,b], based on the notion of A^I-summability. We construct an example to exhibit that the main result is more generalized than its statistical A-summable version. We also study the rate of A^I-summability.